PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA MUSEUM KARS DALAM PEMBELAJARAN IPS UNTUK MENINGKATKAN PEMAHAMAN TERHADAP SITUS SEJARAH PADA SISWA KELAS VII SMP NEGERI 1 NGADIROJO KABUPATEN WONOGIRI TAHUN 2015/2016 - Sutarjo, S.; Sariyatun, S.; Agung S., Leo (HISTORIKA, 2016)
The objectives of this action research is to know (1) The implementation of Problem Based Learning in teaching of Social studies with Kars Museum as the media can improve the students understanding of history site of VII IPS students of SMP Negeri 1 Ngadirojo academic year 2015/2016. (2) The implementation of Problem Based Learning in teaching of Social studies with Kars Museum can improve the students achievement learning of VII IPS students of SMP Negeri 1 Ngadirojo academic year 2015/2016. The methods of this study is Classroom Action Research in two cycles. The subject of this research is the students of VIIE of SMP Negeri 1 Ngadirojo sub-province Wonogiri academic year 2015/2016. Object of the research is teaching learning process that consist of creativity and students activities in teaching learning process, the implementation in history site and the achievement learn of students.The result of this study shows that the implementation of Problem Based Learning in the teaching of Social Studies with Kars Museum as the Media of the students of VIIE class of SMP N 1 Ngadirojo sub-province Wonogiri that held in two cycles (1) result of the study show that the implementation of Problem Based Learning in the teaching of Social Studies with Kars Museum as the media of the students of VIIE class of SMP N 1 Ngadirojo sub-province Wonogiri can improve the students understanding of history site. In cycle I, student which have understanding of history site pertained high and very high is 60,71% then there is an improvement to the history site in cycle II, the students which have understanding of history site pertained high and very high about 85,71% so the students understanding to the history site pertained high more than 85%. (2) There are 10 students that increase on the score of the achievement learning of the students passing grade from the cycle pre that get score as the passing grade or more from the passing grade, in the cycle I increase become 21 students (75,00%), in the cycle II increase become 25 students (89,29%). The average value increase from cycle I 74,64 to 79,64 in cycle II.